Migrant Women in Crisis: Humanitarian Protection Gaps in Global Labor Migration and Lessons for Nepal - Bhattarai, Sabita (NCWA Annual Journal, 2026)
Global labor migration has long been promoted as a pathway to economic empowerment for women in the Global South. However, recent global labor shocks, armed conflicts, pandemics, and geopolitical crises have exposed deep humanitarian protection gaps for migrant women across migration corridors. This article examines how these crises disproportionately affect migrant women, rendering them vulnerable to exploitation, abuse, trafficking, and abandonment, particularly in conflict zones and destination countries with weak labor and protection regimes. Using Nepal as a focal case, the paper adopts a qualitative, policy-oriented approach drawing on secondary literature, international legal instruments, humanitarian reports, and documented crisis responses. The analysis highlights three critical findings: first, humanitarian protection frameworks remain poorly integrated into labor migration governance; second, migrant women are systematically excluded from emergency response mechanisms during crises; and third, Nepal’s existing migration governance prioritizes remittances over rights-based protection. The article argues that Nepal’s foreign policy and labor diplomacy must shift from reactive consular assistance to proactive humanitarian protection mechanisms embedded across the migration cycle. The paper concludes by proposing policy lessons for Nepal, including gender-responsive labor diplomacy, crisis preparedness, and stronger bilateral and multilateral engagement to safeguard migrant women’s rights in an increasingly unstable global labor market